Early Development of Resident Macrophages in the Mouse Cochlea Depends on Yolk Sac Hematopoiesis - Kishimoto, Ippei; Okano, Takayuki; Nishimura, Koji; Motohashi, Tsutomu; Omori, Koichi (Frontiers in Neurology, 2019)
Resident macrophages reside in all tissues throughout the body and play a central role in both tissue homeostasis and inflammation. Although the inner ear was once believed to be “immune-privileged,” recent studies have shown that macrophages are distributed in the cochlea and may play important roles in the immune system thereof. Resident macrophages have heterogeneous origins among tissues and throughout developmental stages. However, the origins of embryonic cochlear macrophages remain unknown. Here, we show that the early development of resident macrophages in the mouse cochlea depends on yolk sac hematopoiesis. Accordingly, our results found that macrophages emerging around the developing otocyst at E10.5 exhibited dynamic changes in distribution and in situ proliferative capacity during embryonic and neonatal stages. Cochlear examination in Csf1r-null mice revealed a substantial decrease in the number of Iba1-positive macrophages in the spiral ganglion and spiral ligament, whereas they were still observed in the cochlear mesenchyme or on the intraluminal surface of the perilymphatic space. Our results demonstrated that two subtypes of resident macrophages are present in the embryonic cochlea, one being Csf1r-dependent macrophages that originate from the yolk sac and the other being Csf1r-independent macrophages that migrate from the fetal liver via systemic circulation. We consider the present study to be a starting point for elucidating the roles of embryonic cochlear resident macrophages. Furthermore, resident macrophages in the embryonic cochlea could be a novel target for the treatment of certain diseases, such as congenital hearing loss due to cytomegalovirus infection.